Evaluating a strain energy fatigue method using cyclic plasticity models - Shahrooi, S.; Metselaar, I.H.; Huda, Z. (2010)
For the development of constitutive equations that describe the behaviour of materials under cyclic plastic strains, different kinds of formulations can be adopted. Recently, an energy-based fatigue damage parameter has been developed to present energy-fatigue life curves using a calculation of the total strain energy. In this study, the damage criterion is examined by calculation of the plastic strain energy from stress-strain hysteresis loops in the cyclic plasticity models under condition of multi-axial fatigue. These cyclic plasticity models are the Garud multi-surface model and the Chaboche nonlinear kinematic hardening model. The models are briefly explained and the general features of their computational procedure are presented. Then, the hysteresis loops of these models will be obtained and the fatigue lives are predicted and compared to experimental data by the ratio of predicted life to experimental life. Consequently, a weighting factor on shear plastic work is presented to decrease the life factors.